Loss of TARBP2 Drives the Progression of Hepatocellular Carcinoma via miR-145-SERPINE1 Axis - Li, Li-Man; Chen, Chang; Ran, Ruo-Xi; Huang, Jing-Tao; Sun, Hui-Lung; Zeng, Chang; Zhang, Zhou; Zhang, Wei; Liu, Song-Mei (Frontiers in Oncology, 2021)
The clinical outcomes of hepatocellular carcinoma (HCC) remain dismal. Elucidating the molecular mechanisms for the progression of aggressive HCC holds the promise for developing novel intervention strategies. The transactivation response element RNA-binding protein (TRBP/TARBP2), a key component of microRNA (miRNA) processing and maturation machinery has been shown to play conflicting roles in tumor development and progression. We sought to investigate the expression of TARBP2 in HCC using well-characterized HCC cell lines, patient-derived tissues and blood samples. Additionally, the potential prognostic and diagnostic value of TARBP2 in HCC were analyzed using Kaplan-Meier plots and ROC curve. Cell counting kit‐8 (CCK‐8), wound healing and transwell assays examined the ability of TARBP2 to induce cell proliferation, migration, and invasion in HCC cell lines. RNA sequencing was applied to identify the downstream elements of TARBP2. The interaction of potentical targets of TARBP2 , miR‐145 and serpin family E member 1 (SERPINE1), was assessed using luciferase reporter assay. TARBP2 expression was down-regulated in HCC cell lines relative to normal hepatocyte cells, a similar pattern further confirmed in tissue and blood samples. Notably, the loss of TARBP2 was demonstrated to promote proliferation, migration, and invasion in HCC cell lines. Interestingly, the reduction of TARBP2 was shown to result in the upregulation of SERPINE1, also known as plasminogen activator inhibitor (PAI-1), which is a vital gene of the HIF-1 signaling pathway. Knockdown of SERPINE1 rescued the TARBP2-lost phenotype. Moreover, TARBP2 depletion induced the upregulation of SERPINE1 through reducing the processing of miR-145, which directly targets SERPINE1. Finally, overexpression of miR-145 repressed SERPINE1 and rescued the functions in sh-TARBP2 HCC cells. Our findings underscore a linear TARBP2-miR-145-SERPINE1 pathway that drives HCC progression, with the potential as a novel intervention target for aggressive HCC.